Corporate modular display the development of customized point of sale structures to a new approach of modular retailing system for the grocery channel - Reyes, Vanessa Marie F.
Point of sale displays are, most of the times, customized. They last in the market for maximum of one year depending on the material use. For most POS materials, sintra board, which is made of plastic, is most commonly used. The increase of garbage in the Philippines is uncontrollable. With this, I came up with a modular point of sale display using recyclable materials and the communication tool fully recyclable, made out of paper. "Corporate Modular Display" is designed to handle all types of packaging, fully recyclable and fit for all spaces.